LATTICE SPECTRUM WITH DYNAMIC STAGGERED QUARKS AT 6/G2 = 5.6 - Bitar, K; Degrand, T; Edwards, R; Gottlieb, S; Heller, U; Kennedy, A; Kogut, J; Krasnitz, A; Liu, W; Ogilvie, M; Renken, R; Rossi, P; et al. (1991)
Under the DOE Grand Challenge program, we have calculated the hadron spectrum of QCD with two flavors of dynamical quarks. We set 6 g2 = 5.6 and use bare quark masses amq = 0.025 and 0.01 to generate gauge configurations. The spectrum is calculated using both staggered and Wilson valence quarks. There are several positive features when these results are compared to those with larger lattice spacing; however, the nucleon to rho mass ratio is still too large. © 1991.